The role of IL‑16 gene polymorphisms in endometriosis - Matalliotakis, M; Zervou, M; Eliopoulos, E; Matalliotaki, C; Rahmioglu, N; Kalogiannidis, I; Zondervan, K; Spandidos, D; Matalliotakis, I; Goulielmos, G (Spandos Publications, 2018)
Endometriosis is one of the most common gynecological diseases affecting up to 10% of the female population of childbearing age and a major cause of pain and infertility. It is influenced by multiple genetic, epigenetic and environmental factors. Interleukin‑16 (IL‑16) is a proinflammatory cytokine playing a pivotal role in many inflammatory and autoimmune diseases as well as in the pathogenesis of endometriosis. The aim of the present study was to evaluate the association of two IL‑16 gene single nucleotide polymorphisms (SNPs), rs4072111 and rs11556218, with the risk of endometriosis in women from Greece as well as to gain insight about the structural consequences of these two exonic SNPs regarding development of the disease. A total of 159 women with endometriosis (stages I‑IV) hospitalized for endometriosis, diagnosed by laparoscopic intervention and histologically confirmed, and 146 normal controls were recruited and genotyped. Subjects were genotyped using a polymerase chain reaction restriction fragment length polymorphism (PCR‑RFLP) strategy. A significant association was detected regarding the GG and GT genotype as well as 'G' allele of rs11556218 in patients with endometriosis. The rs4072111 SNP of the IL‑16 gene was not found to be associated with an increased susceptibility to endometriosis either for all patients (stages I‑IV) or for stage III and IV of the disease only. Our results demonstrated that rs11556218 is associated with endometriosis in Greek women, probably by resulting in the aberrant expression of IL‑16, as suggested by the bioinformatics analysis conducted on the SNP‑derived protein sequences, which indicated a possible association between mutation and functional modification of Pro‑IL‑16.